PERAN GURU DALAM MENINGKATKAN KEDISIPLINAN PADA ANAK USIA DINI - Ulfa, Magvira; Ias Nugrahani (EDUCHILD (Journal of Early Childhood Education), 2026)
The purpose of this article is to determine the role of teachers in improving discipline in early childhood in Class A of TKIT Asshiddiq, Tanete Riattang Barat District, Bone Regency. This study uses a qualitative research type. The data sources in this study are teachers and students in TKIT Asshiddiq class A, totaling 2 teachers and 11 students. Data collection techniques used in this study are observation, interviews and documentation. Qualitative data processing techniques consist of three stages of activities, namely: reducing data, presenting data, and drawing conclusions and verification. The results of the study indicate that the role of teachers in improving discipline in early childhood is as role models, guides, facilitators, and reinforcers of positive behavior. Keywords: the role of the teacher, discipline